MAPPING THE THEME UNDERLYING THE LITERATURE ON GREEN FINANCE: A CONTEMPORARY STRATEGY FOR SUSTAINABILITY - Muhammad Akram; Muhammad Umer Quddoos; Muhammad Aamir (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
With growing global concern towards world sustainability, Green Finance has been growing as one of the tools to achieve sustainable development goals. Sustainable development has directed the attention of policymakers and researchers towards green finance. This study aims to formulate the strategy of sustainability by conducting a bibliometric analysis exploring the growth and academic evolution of green finance. The study is grounded on a sample of 649 articles retrieved from the Scopus database during the period of three decades from 1994 to 2023. VOS viewer software was employed to display and analyze the data. The results investigate the several facets of green finance as publication trends, citations, country collaboration, core sources, authorship networks, and development phases. The results indicate a significant rise in academic and industry interest. China is observed as a leader in the realm of green finance. UK ranked second, similarly after that USA, Japan, and Pakistan ranked in the swift growth of green finance. The analysis delves into highly role of public policies, government decisions and initiatives, private sector motivation in green investments, green projects, and sustainability development. The analysis also investigates critical developments, the researcher and scholar’s influential publications and contributions, geographical and conceptual domain, and concentration on defining this critical emerging field. The results provide some practical implications for the bankers, individuals, financial institutions, researchers, policymakers, government, and society for achieving sustainable development goals with a number of prospective future research avenues, including green investment, green policies, green financial regulation, Artificial Intelligence, and green financial technology applications.